Perinatal Oxidative Stress and Kidney Health: Bridging the Gap between Animal Models and Clinical Reality - You-Lin Tain; Chien-Ning Hsu (MDPI AG, 2022)
Oxidative stress arises when the generation of reactive oxygen species or reactive nitrogen species overwhelms antioxidant systems. Developing kidneys are vulnerable to oxidative stress, resulting in adult kidney disease. Oxidative stress in fetuses and neonates can be evaluated by assessing various biomarkers. Using animal models, our knowledge of oxidative-stress-related renal programming, the molecular mechanisms underlying renal programming, and preventive interventions to avert kidney disease has grown enormously. This comprehensive review provides an overview of the impact of perinatal oxidative stress on renal programming, the implications of antioxidant strategies on the prevention of kidney disease, and the gap between animal models and clinical reality.